PEMANFAATAN LIMBAH MINYAK JELANTAH MENJADI PRODUK YANG BERNILAI EKONOMIS DI KOTA SEMARANG - Yani, Tri Endang; Wibisono, Totok; Roestanto, Anantya; Sujito, Sujito (Jurnal Abdimas Bina Bangsa, 2025)
Used cooking oil is often thrown away rather than utilized. This will certainly endanger the environment. In fact, this used cooking oil can actually be turned into useful products. Therefore, it is very important to educate the public about the dangers of used cooking oil waste to the environment and how to utilize it. The target of this community service is mothers who are UMKM actors in Krobokan Village, West Semarang. The purpose of Community Service is to provide education about the dangers of used cooking oil to the environment and provide training on utilizing used cooking oil into products with economic value, namely aromatherapy candles. The method of implementing community service activities is the socialization and training method. After participating in this community service activity, there was an increase in public awareness of the dangers of used cooking oil waste and an increase in skills in utilizing used cooking oil into products with economic value. This activity is expected to contribute to waste management and can create profitable business opportunities.